2021
DOI: 10.3390/cancers13102466
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Dabrafenib and/or Dabrafenib Plus Trametinib Combination in Patients with Metastatic Melanoma to Characterize Patients with Long-Term Benefit in the Individual Patient Program (DESCRIBE III)

Abstract: The dabrafenib plus trametinib (dab + tram) combination has demonstrated durable long-term efficacy in patients with BRAF V600–mutant metastatic melanoma. However, real-world data characterizing patients with long-term benefit are limited. DESCRIBE III was a global, observational, retrospective, chart review study in patients with unresectable or metastatic melanoma treated with dab monotherapy and/or dab + tram combination therapy as part of the Named Patient Program or Individual Patient Program. Overall, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
4
4
0
Order By: Relevance
“…Three real-world studies (DESCRIBE I (N = 331), DESCRIBE II (N = 271), and DESCRIBE III (N = 509)) evaluated the treatment patterns and clinical outcomes in patients with BRAF V600-mutant unresectable or metastatic melanoma enrolled in the Named Patient Program who were treated with dab monotherapy and/or dab + tram combination therapy. The efficacy and safety outcomes in these studies were consistent with those reported in the randomized controlled clinical trials [4][5][6].…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Three real-world studies (DESCRIBE I (N = 331), DESCRIBE II (N = 271), and DESCRIBE III (N = 509)) evaluated the treatment patterns and clinical outcomes in patients with BRAF V600-mutant unresectable or metastatic melanoma enrolled in the Named Patient Program who were treated with dab monotherapy and/or dab + tram combination therapy. The efficacy and safety outcomes in these studies were consistent with those reported in the randomized controlled clinical trials [4][5][6].…”
Section: Introductionsupporting
confidence: 81%
“…Compassionate-use programs provide an opportunity to retrospectively evaluate the treatment patterns and clinical outcomes in a real-world setting and are critical tools in extending and confirming the results derived from randomized controlled clinical trials. Three real-world studies (DESCRIBE I, DESCRIBE II, and DESCRIBE III) assessed the treatment patterns and clinical outcomes of the therapies evaluated in the BREAK trials (dab monotherapy) and the COMBI-d and COMBI-v trials (dab + tram combination therapy) and demonstrated consistency with these previous pivotal clinical trials [4][5][6].…”
Section: Discussionmentioning
confidence: 87%
“…In patients with limited disease and brain or skin metastasis, OS was not reached, while in patients with bulky disease and brain metastasis, OS was longer (8 months) than that reported in patients with liver metastasis (6.8 months). These results were consistent with the analyses of the retrospective study DESCRIBE III, which categorized patients according to three benefit groups based on the observed duration of treatment within the Nominal Patient Program/Individual Patient Program [ 15 ]. In this study, brain metastases were similar across all groups (short-term, 22.1%; long-term, 17.3%), while liver metastases were the highest in the short-term duration of the benefit group (short-term, 28.3%; long-term, 11.1%), thus corroborating the notion that the site of metastasis affects the clinical response to therapy [ 15 ].…”
Section: Discussionsupporting
confidence: 87%
“…These results were consistent with the analyses of the retrospective study DESCRIBE III, which categorized patients according to three benefit groups based on the observed duration of treatment within the Nominal Patient Program/Individual Patient Program [ 15 ]. In this study, brain metastases were similar across all groups (short-term, 22.1%; long-term, 17.3%), while liver metastases were the highest in the short-term duration of the benefit group (short-term, 28.3%; long-term, 11.1%), thus corroborating the notion that the site of metastasis affects the clinical response to therapy [ 15 ]. In the retrospective study DESCRIBE II, patients who were naïve to B-RAF inhibitors were analyzed by the brain metastases’ status at treatment initiation [ 16 ].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, elderly patients have a different fever response as response of infection, being fever more unusual symptom than younger patients [20][21][22][23]. Although the proportion of patients with some selected AEs and, in particular pyrexia, was lower than that reported in phase 3 trials, the results in this study are similar to what has been reported in other real-world analyses for dabrafenib and trametinib [16,24]. This may be at least in part due to a general underreporting of AEs in studies of retrospective nature.…”
Section: Discussionsupporting
confidence: 85%